الخدمات المالية الرقمية كآلية لتعزيز الشمول المالي دراسة حالة تجارب دولية - كينيا، الهند، الإمارات - - نجاة, مجوري; عواطف, عتيق نصر (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة إلى إبراز مساهمة الخدمات المالية الرقمية في تعزيز الشمول المالي، لتحقيق أهدافه وتطوير الخدمات المالية والمصرفية الرقمية، وذلك من خلال عرض لتجارب دولية رائدة، ولتحقيق هدف الدراسة، ركزنا على أساسيات التكنولوجيا المالية والتحول الرقمي والخدمات المالية الرقمية، وأيضا أساسيات الشمول المالي، مستخدمين بذلك المنهج الوصفي، ثم عرض واقع الخدمات المالية الرقمية، وتحليل مؤشرات الشمول المالي الدالة على تحقيقه باعتماد أسلوب استقراء و دراسة حالة كل من دولة كينيا والهند والإمارات في مجال اعتماد الخدمات المالية الرقمية. وتوصلت الدراسة إلى فعالية التجارب محل الدراسة في مجال تعزيز الشمول المالي وتوسيع نطاقه، ففي كينيا يعود نجاح التجربة إلى اعتماد خدمة الهاتف المحمول M-Pesa، بينما الهند فكان أساس نجاحها مبني على اعتماد نظام الهوية الرقمية ""آدهار""، أما الإمارات فقد اعتمدت على دور الشركات الناشئة في مجال التكنولوجيا المالية، وتؤكد ذلك قاعدة بيانات البنك العالمي(findex) التي تشير فيها مؤشرات الشمول المالي إلى مستويات عالية باتجاه تعميق انتشار الشمول المالي والتي كانت لجهود الدول السابقة الذكر الدور الداعم في تعزيز الشمول المالي من توفير بنى تحتية، وتثقيف مالي. "" This study aims to highlight the digital financial services contribution in promoting financial inclusion and achieving its objectives, and developing digital financial and banking services, through a reviewing of leading international experiences. In attempt to accomplish its objective, the study focused the reality of digital financial services, the financial technology basics, digital transformation and digital financial services, as well as the basics of financial inclusion, using the descriptive approach. The study presents the digital financial services reality, and analyzes the indicators of financial inclusion that indicates its achievement by adopting an extrapolation method and studying the cases of Kenya, India and the UAE in the field of adopting digital financial services. The study concluded that the effectiveness of the experiments studied in the field of promoting and expanding financial inclusion. In Kenya, the success of the experiment is due to the adoption of the M-Pesa mobile phone service, whereas India's experiment was based on the adoption of the digital identity system “Aadhar”, while in the UAE it was relied on the role of startup companies in the field of financial technology. Which is confirmed by the World Bank database (findex) where the indicators of financial inclusion indicate high levels towards deepening the spread of financial inclusion, and the aforementioned countries efforts had a supportive role in promoting financial inclusion by providing infrastructures and financial education."
ماستر اقتصاد
Keywords: تكنولوجيا مالية، تحول رقمي، خدمات مالية رقمية، شمول مالي.; Financial technology, Digital transformation, Digital financial services, financial inclusion.